Quantity of within-sport distance variety – what can pool swimmers and track runners learn from each other? - Born, Dennis-Peter; Lorentzen, Jenny; Björklund, Glenn; Ruiz-Navarro, Jesús J. (Frontiers in Sports and Active Living, 2024)
Objective To determine the relationship between success at peak performance age and quantity of within-sport distance variety and compare the dose-time-effect between swimming and track running by determining probability of becoming an international-class female athlete based on the number of different race distances the athletes compete in each year throughout their development process. Methods Race times of female Tier 2 to Tier 5 freestyle pool swimmers (n = 2,778) and track runners (n = 9,945) were included in the present study. All athletes were ranked according to their personal best at peak performance age. Subsequently, number of different race distances during each year were retrospectively extracted from peak performance to early junior age. Personal best performance points at peak performance age were correlated with the number of different race distances across the various age categories. Poisson distribution determined the dose-time-effect of becoming an international-class athlete based on the number of different swimming strokes. Results At peak performance age, correlation analysis showed a larger within-sport distance variety for higher ranked athletes, particularly for track runners (r ≤ 0.35, P < 0.001). Despite reaching statistical significance, the effects were small to moderate. While swimmers showed a generally larger within-sport distance variety than track runners, Poisson distribution revealed a dose-time-effect for the probability of becoming an international-class swimmer. Sprint and middle-distance swimmers benefit from competing in three race distances during junior age and a transition to two race distances at 17–18, 18–19, 20–21 and 25–26 years of age for 50 m, 100 m, 200 m and 400 m races, respectively. Long-distance swimmers should maintain three different race distances throughout peak performance age. Probability analysis showed a consistent benefit of competing in one or two race distances for 100 m, 200 m, 400 m and 800 m track runners. Conclusion Within-sport distance variety is not a continuum but an ever-evolving process throughout the athletes' careers. While swimmers generally show larger variety than track runners, the progressive specialization towards peak performance age improves success chances to become an international-class swimmer.